The Transport Service of Small Towns - Jozef Gnap; Jana Kupčuljaková; Ľubomír Černický; Grzegorz Dydkowski (Communications - Scientific letters of the University of Zilina, 2021)
The paper is focused on assessment of the transport services in small towns. Current legislation in the Slovak Republic, however, does not clearly determine which cities must provide the urban public transport (UPT). Analysis of the current state of the UPT evaluated 71 district towns of the SR and it was found out that 21 towns did not provide operation of the UPT. Another criterion for evaluation was the number of inhabitants of the city over 10,000 in Slovakia and selected regions of the Czech Republic and Poland. The paper presents results of a research conducted in the area of a transport operation, along with a proposal for the content of the methodology, based on a multi-criterial analysis to assess the need to introduce the UPT. The EU research results, regarding dependency of a GDP size and transport performances in UPT in selected EU states, Switzerland and Norway, are presented, as well.